Identifying Resilience Factors of Distress and Paranoia During the COVID-19 Outbreak in Five Countries - Mækelæ, Martin Jensen; Reggev, Niv; Defelipe, Renata P.; Dutra, Natalia; Tamayo, Ricardo M.; Klevjer, Kristoffer; Pfuhl, Gerit (Frontiers in Psychology, 2021)
The ongoing COVID-19 pandemic outbreak has affected all countries with more than 100 million confirmed cases and over 2.1 million casualties by the end of January 2021 worldwide. A prolonged pandemic can harm global levels of optimism, regularity, and sense of meaning and belonging of people, yielding adverse effects on individual's mental health as represented by worry, paranoia, and distress. Here we studied resilience, a successful adaptation despite risk and adversity, in five countries: Brazil, Colombia, Germany, Israel and Norway. In April 2020, over 2500 participants were recruited for an observational study measuring protective and obstructive factors for mental health. More than 800 of these participants also completed a follow-up study in July. We found that thriving, keeping a regular schedule, engaging in physical exercise and less procrastination served as factors protecting mental well-being. Risk factors were financial worries and a more negative mindset, e.g. feeling a lack of control. Longitudinally, we found no increase in distress or paranoia despite an increase in expectation how long the outbreak and the restrictions will last, suggesting respondents engaged in healthy coping and adapting their life to the new circumstances. Thus our data shines some light on the mostly depressive news during the pandemic. Humans adapt and despite adversity there are protective factors that policy makers should leverage on.